Continuous Fascia Iliaca Compartment Block for Post Operative Analgesia in Fracture Femur - Shakya, Bigen Man; Shrestha, Ninadini (Journal of Nepal Health Research Council, 2018)
The postoperative pain management in the elderly is challenging due to comorbidities and change in physiology due to age itself. This limit the use of medication which include pain medication also. The fascia iliaca compartment block has been described in the literature for fracture of femur. It has even been safely used by non anaesthesiologist also. To our knowledge, we did not find any case report of continuous fascia iliaca compartment block published in Nepal. This is our first experience of successful continous fasicia iliaca compartment block in case of 89 year old lady with multiple co morbidities in whom traditional pain medication might be difficult to use. We encourage to practice this block which is both safe and easy to perform with good results. Keywords: Continous fascia iliaca compartment block.